Students’ Perception on The Utilization of Google Classroom in Studying English Writing Skill - Annisa Mifta Huljannah; Abd. Kamaruddin; Anjar Kusuma Dewi (Syntax Corporation Indonesia, 2024)
The purpose of the present research is to find out the real fact of the students’ perception on the utilization of Google Classroom in the teaching of writing skill. This research is a qualitative design. The subject of the research was the Second Semester of Grade Eleventh students of Madani Senior High School that consisted of 33 participants. The participants were selected by purposive sampling. The data were collected using interview and analyzed using Likert Scale. The researcher found that there were four category of students’ perceptions toward the dimension of Google Classroom in Teaching Writing Skill in which the students were mostly agree with; (1) the average students’ response to the use of Google Classroom is 75, 8 % of the total number of students, (2) the average students’ response to the use of Google Classroom in the teaching of writing skill is 75, 8% of the total number of students, (3) the average students response to the impact of the using of Google Classroom in teaching writing skill is 69, 7% of the total number of students, and (d) the average students’ response related to their satisfactory toward the use of Google Classroom in the teaching Writing Skill is 69, 7% of the total number of students. It means that the students have positive response toward the use of Google Classroom platform in teaching and learning English. It implies that the use of the Google Classroom platform to teach Writing Skill is enable students to have good motivation in studying writing skill.